Mottes castrales en Provence Les origines de la fortification privée au Moyen Âge - Mouton, Daniel (Documents d'archéologie française, 2008)
Two decades of research on Motte-and-Bailey castles in Provence have contributed new elements to our knowledge of the castle phenomenon that developed at the end of the 10th century. More than sixty sites have been recorded and our prospection continues to reveal new ones. The excavation of several of them allowed us to identify the evolution of construction methods and the organization of these small castles. In the beginning, they were very modest edifices consisting of simple perched houses that required relatively few resources and employed techniques that were easy to put into operation. In the second phase, beginning around 1000 AD, we observe the construction of true fortresses. The study of these first fortifications focuses on the occupation of terroirs organized around a castrum, often noted in texts. The construction of these fortifications seems to have been most intensive around 1000 AD and during the 11th century, but some were erected at the beginning of the 13th century. This ongoing research shows that the early stages of private fortification was integrated in a vast trend of the occupation of terroirs surrounding complex fortifications.